Information and Communication Technologies in Tourism 2022 Proceedings of the ENTER 2022 eTourism Conference, January 11-14, 2022 - Stienmetz, Jason L.; Ferrer-Rosell, Berta; Massimo, David (Springer International Publishing : Imprint: Springer, 2022)
This open access book presents the proceedings of the International Federation for IT and Travel & Tourism (IFITT)'s 29th Annual International eTourism Conference, which assembles the latest research presented at the ENTER2022 conference, which will be held on January 11-14, 2022. The book provides an extensive overview of how information and communication technologies can be used to develop tourism and hospitality. It covers the latest research on various topics within the field, including augmented and virtual reality, website development, social media use, e-learning, big data, analytics, and recommendation systems. The readers will gain insights and ideas on how information and communication technologies can be used in tourism and hospitality. Academics working in the eTourism field, as well as students and practitioners, will find up-to-date information on the status of research.